SERANGGA HAMA YANG BERASOSIASI PADA TANAMAN PEPAYA (Carica papaya L.) DI DESA TALAWAAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Feybra S. Sigarlaki; Jantje Pelealu; James B. Kaligis; Emmy Senewe (COCOS, 2014)
ABSTRACTFeybra S. Sigarlaki. Pest Insects Associated on Plants Papaya (Carica Papaya L.) in the Village Talawaan, District Talawaan, Regency Minahasa Utara. Under Guidence Prof. Dr. Ir. Jantje Pelealu, MS as chairman, Ir. James B. Kaligis, M.Si and Ir. Emmy Senewe, M.Si as member.The study aimed to determine the association of insect pests on crop Papaya in Village Talawaan, District Talawaan, regency Minahasa Utara. Research conducted surveys using methods purporsive sampling. At planting area observed insects found in papaya plants. Sampling was done by catching insects directly and observe the plants in the form of stems, leaves, and fruit are infested by insects. Insect samples were obtained from the direct retrieval, collected and grouped then taken to the laboratory for identification and documentation. Insect samples were taken on three varieties of papaya, the varieties of Bangkok, Thailand and California. Each set of 20 varieties of trees as a place of observation. The total number of papaya plants sampled 60 trees. Sampling was carried out four times at intervals of two weeks. Things that are observed insects collected on various varieties of papaya.The results of the study found four types of insects that are associated to the papaya plant in the Village Talawaan, District Talawaan. Types of insect pests, namely Aleurodicus sp. (Hemiptera: Aleyrodidae) and Paracoccus sp. (Hemiptera: Pseudococcidae) and their natural enemies, the Coccinellidae (Coleoptera) and Forficulidae (Dermaptera).Keywords : Carica papaya, Minahasa Utara